2021
DOI: 10.1371/journal.pone.0252690
|View full text |Cite
|
Sign up to set email alerts
|

Malaria risk factors in northern Namibia: The importance of occupation, age and mobility in characterizing high-risk populations

Abstract: In areas of low and unstable transmission, malaria cases occur in populations with lower access to malaria services and interventions, and in groups with specific malaria risk exposures often away from the household. In support of the Namibian National Vector Borne Disease Program’s drive to better target interventions based upon risk, we implemented a health facility-based case control study aimed to identify risk factors for symptomatic malaria in Zambezi Region, northern Namibia. A total of 770 febrile indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…These factors will also be increasingly feasible to account for in future models, as data quantity and quality, especially in routine data, as well as modelling capacities continue to improve. Similarly, urban and rural councils only differed in their transmission intensity and setting specific parameters for seasonality and intervention coverage, whereas socio-demographic factors [ 82 ], population density [ 83 ], local environment and infrastructure [ 84 ], as well as human mobility malaria case importation rates [ 85 , 86 ] among other factors that are important considerations for intervention implementation were not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…These factors will also be increasingly feasible to account for in future models, as data quantity and quality, especially in routine data, as well as modelling capacities continue to improve. Similarly, urban and rural councils only differed in their transmission intensity and setting specific parameters for seasonality and intervention coverage, whereas socio-demographic factors [ 82 ], population density [ 83 ], local environment and infrastructure [ 84 ], as well as human mobility malaria case importation rates [ 85 , 86 ] among other factors that are important considerations for intervention implementation were not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that school-aged children are less well-covered by LLINs [ 10 , 12 , 28 ]. These older children are often overlooked by malaria control strategies, which have traditionally focused on children under-five and pregnant women who typically bear the burden of malaria morbidity and mortality in higher transmission areas [ 29 , 30 ]. Older children, who have developed anti-disease immunity through repeated exposure, are often asymptomatic when infected with malaria parasites.…”
Section: Discussionmentioning
confidence: 99%
“…These regions are characterized by low levels of vector control coverage, mobile and migrant populations, and some of Namibia's lowest malaria reporting rates. 15,16 Kavango East and Kavango West have separate political administrations of elected officials-namely, Regional Councils and Regional AIDS Coordinating Committees (RACOC)but their health programs are managed by a shared Regional Management Team and are supported by four district coordinating committees.…”
Section: Methodsmentioning
confidence: 99%